Access to Food Within Homes Located in Very Remote Communities in Western Australia—An Observational Study - Melissa Stoneham; Christina Mary Pollard (Health Promotion Journal of Australia, 2026)
ABSTRACT Introduction Food insecurity contributes substantially to the gap in health outcomes between Aboriginal and Torres Strait Islander peoples and non‐Indigenous Australians, particularly in remote communities where household infrastructure may limit the safe storage and preparation of food. Methods This direct observational study aimed to measure access to food storage infrastructure and availability as indicators relevant to food security within homes in very remote Aboriginal communities in Western Australia. Researchers, accompanied by a local Aboriginal Environmental Health Worker, used a purpose‐built mobile audit tool to document the presence and functionality of refrigerators, freezers and pantries and food available in houses in 18 very remote desert communities. Results In total, 185 homes were audited. At the time of audit, 58 homes (31%) had no food stored in the refrigerator, freezer or pantry. The majority of homes had a refrigerator and/or freezer, although 20% had neither. Conclusion Inadequate household facilities for safe food storage increase the likelihood of food insecurity in very remote communities, with implications for diet quality, household costs and reliance on frequent purchasing or convenience foods. Strategies to improve food security should include investment in and maintenance of functional kitchen infrastructure. So What? Safe and functional housing is vital for health and wellbeing. This type of research is unique. It identified that many Aboriginal Australian Peoples living in remote Western Australia face barriers to appropriate and sustainable living conditions and health hardware needed to ensure food storage and food security in the home environment. Addressing these issues is critical to achieving Closing the Gap and promoting healthy families.